Feminist new materialisms: Activating Ethico-Politics Through Genealogies in Social Sciences - Rogowska-Stangret, Monika (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
For the editors of this collection, new materialisms have always been the entanglement of epistemology, ontology, ethics, and politics. Looking back to the notion of "situated knowledges" (Haraway, 1988) that - among others - "planted the seed for feminist new materialism" (van der Tuin, 2015, 26) - one sees how those (at least) four planes are entangled (Rogowska-Stangret, 2018) in order to bring forth "response-able" (Haraway, 2008) research. New materialism is thus an ethico-onto-epistemological framework (Barad, 2007; Revelles-Benavente, 2018) that by activating its ethico-politics helps to diagnose, infer, and transform gendered, environmental, anthropocentric, social injustices from a multidimensional angle. Social injustices are a driving motivation to pursue research and are the reason why the editors and authors of this Special Issue cannot understand new materialism without feminism (in the lines of eds. Hinton & Teusch, 2015). Contemporary feminist researchers are providing new materialisms with a transversal approach, (Yuval-Davis 1997) that comes from many different disciplines without canonizing back again knowledge creation and production and in hope that they will not enter back into classifixations (van der Tuin, 2015). It is "situated" (Haraway, 1988) research "response-able" (Haraway, 2008) to material-discursive practices that iterate in a dynamic conceptualization of matter.